Needs Analysis for Virtual Reality-based Safety Training Spotting Hazards in the Commercial Kitchens - Saad, Mazni; Haminuddin, Norsuhana; Jeinie, Mohamad Halim; Abdullah, Norhidayah; Sahrir, Muhammad Sabri; Mokhtar, Mohd Khalid (Science Cite, 2024)
Literature highlights kitchen safety issues related to deficiencies in safety training, and a lack of in-depth knowledge of hazard identification and worker safety, time constraints in educating commercial kitchens employees on safety. The fast-paced nature of the industry often overlooks safety measures. To address this, leveraging virtual reality (VR) technology is proposed for comprehensive hazard training in kitchens, a versatile tool recognized in education, medicine, and engineering. Hence, two-fold questions are: (1) What is the needs analysis in designing a VR-based safety training spotting hazards in the commercial kitchen and (2) what is the needs analysis in designing of preparation for VR-based safety training in the commercial kitchen. This study employs a Training Needs Analysis (TNA) methodology with 12 participants from diverse roles including food handlers, occupational safety and health officer (SHO) and IT executives to assess hazard-spotting practices in commercial kitchens. Utilizing a combination of interviews and on-site observations, the study assesses the current state of hazard awareness and the effectiveness of existing training programs. Notably, limitations include reliance on information solely from staff who attended food safety training. The study unveils a critical gap in last-minute hazard recognition and a lack of comprehensive occupational safety and health training within the kitchen industry. Findings underscore the urgency for targeted interventions. The proposed solution involves a VR-based training program, offering an immersive experience to enhance hazard awareness. This research contributes valuable insights into the pressing need for innovative training strategies to fortify safety protocols in commercial kitchen workplaces.